2021
DOI: 10.1007/s00415-021-10817-x
|View full text |Cite
|
Sign up to set email alerts
|

Brain network topology and future development of freezing of gait in Parkinson’s disease: a longitudinal study

Abstract: Background Freezing of gait (FOG) is a common disabling gait disturbance in Parkinson's disease (PD). The objectives of this study were to explore alterations in the topological organization of whole-brain functional networks in patients with PD who will develop FOG. Methods We recruited 20 patients with PD who developed FOG (PD-FOGt) during a 5-year follow-up period, 20 patients with PD who did not developed FOG (PD-FOGn) within the follow-up period, and 20 healthy control subjects. Using graph theory approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Thus, structural damage to the left gyrus rectus and MCC might impair gait directly or indirectly by affecting external and internal information integration, abstract cognition translation, and links between cognitive and motor systems. Consistently, there is sufficient evidence to demonstrate structural and functional abnormalities of the left gyrus rectus and MCC in PD-FOG (24,26,60). Taken together, our results suggested that FOG in PD is a complex network disorder.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, structural damage to the left gyrus rectus and MCC might impair gait directly or indirectly by affecting external and internal information integration, abstract cognition translation, and links between cognitive and motor systems. Consistently, there is sufficient evidence to demonstrate structural and functional abnormalities of the left gyrus rectus and MCC in PD-FOG (24,26,60). Taken together, our results suggested that FOG in PD is a complex network disorder.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, to reduce the potential confounding effects of emotion, we added the HAMA and HAMD-24 scores as covariates in imaging analyses. Third, previous rs-fMRI studies have elucidated other altered brain regions (such as the middle frontal gyrus and cerebellum) (25,26,63) or networks (such as the dorsal attentional network and visual network) (64,65) in PD-FOG by analyzing functional networks. Such inconsistency may be due to differences in included populations, study methods, and statistical thresholds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have employed EEG signals to investigate the brain function of PD patients. For example, Li et al revealed that EEG BN in PD patients can be implemented to predict the severity of gait freezing [25]. Geraedts et al showed that analysis of EEG BN of PD patients can be used for effective early diagnosis of their non-motor symptoms [26].…”
Section: B4 Assessment Of Mit For Eeg Signals In the Space-time-frequ...mentioning
confidence: 99%
“…26,27,29,33 In addition, visual-related areas also showed abnormal neural activation, and structural and functional changes in PD. [34][35][36] However, whether abnormal neural information stored in sensorimotor, visual, and cognitive-related areas was also unclear.…”
Section: Introductionmentioning
confidence: 99%